ANALISIS PENERAPAN SISTEM INFORMASI PENGELOLAAN BARANG MILIK NEGARA MELALUI APLIKASI SISTEM INFORMASI KENDARAAN DINAS (SIKENDIS) PADA BAGIAN BANGUNAN, SEKRETARIAT KEMENTERIAN SEKRETARIAT NEGARA RI - Purbono, Rio; Patria, Yoka Mai (Jurnal Ilmu Administrasi Publik, 2025)
Management of State Property (BMN) is an important aspect in supporting efficiency, transparency and accountability of government administration. However, challenges such as inaccurate data, weak supervision and manual administrative processes often hinder the effectiveness of managing state assets. To overcome this, the Secretariat of the Ministry of State Secretariat of the Republic of Indonesia developed the Official Vehicle Information System (SIKENDIS) as a digital solution for managing BMN, especially official vehicles. This research aims to analyze the effectiveness of implementing SIKENDIS based on DeLone and McLean (2003) information system success model, which includes the dimensions of system quality, information quality, service quality and usage intentions. The research method used is descriptive-qualitative with data collection techniques through interviews, observation and documentation. The research informants consisted of employees who were directly involved in the operational management of official vehicles using SIKENDIS. The research results show that the implementation of SIKENDIS has had a positive impact on the management of official vehicles, especially in increasing efficiency, administration and transparency. The quality of the system is considered quite good, although it still requires improvements to stability and interface. The quality of the information is considered accurate, however there are obstacles in updating the data due to inconsistent manual input. Service quality received positive reviews, but slow technical response and lack of training were concerns. High perceived usefulness of the system drives usage intention, although initial adaptation for new users takes longer. Overall, the implementation of SIKENDIS contributes significantly to the effectiveness of BMN management of official vehicles. To achieve system sustainability, this research recommends increasing technological capacity, more intensive user training, and system integration with other supporting technologies.